Graft failure of IgA nephropathy in renal allografts following living donor transplantation: predictive factor analysis of 102 biopsies - Zhang, Jin (BMC Nephrol, 2019)
BACKGROUND: To investigate predictive factors related to graft failure of IgA nephropathy(IgAN) in renal allografts following living donor transplantation. METHODS: We identified a series of 102 biopsies diagnosed as IgAN in renal allografts following living donor transplantation from July 2004 to January 2017 at our center, and assess the predict value of the Lee’s classification and the 2009 Oxford classification in IgAN in renal allografts, clinical, ultrasonic and pathological characteristics at biopsy and the outcomes were retrospectively analyzed. RESULTS: The 5-year graft cumulative survival rate after transplantation was 91.4%. The 4-year graft cumulative survival rate after biopsy diagnosis of IgAN in renal allografts was 59.6%. The mean time ± SD to disease was 4.7 ± 3.5 years. The color doppler ultrasound and blood flow imagine showed the echo enhancement, the reduced blood flow distribution, the reduced peak systolic velocity of main renal artery, and the increased resistance index of arcuate renal artery were valuable in evaluating the graft dysfunction. The Cox multivariate analysis revealed that the 24-h urinary protein level (HR 1.6 for 1-g increase, 95%CI 1.2–2.0), estimated glomerular filtration rate (eGFR) (HR 1.0 for 1-mL/min/1.73 m^2 decline, 95%CI 1.0–1.1), and mesangial C1q deposition (HR 3.0, 95%CI 1.2–7.4) at biopsy were independent predictive factors of graft failure of IgAN in renal allografts. CONCLUSIONS: IgAN in renal allografts occurred frequently within 5 years after transplantation. The risk of graft failure should be taken seriously in patients who exhibit heavy proteinuria and/or a declined eGFR as the initial symptoms; a high lesion grade (grade IV-V of Lee’s classification) and/or mesangial C1q deposition may also indicated a poor outcome.